2017
DOI: 10.1021/acs.jpcb.7b04634
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of Ionic Pair Dissociation in a Lithium Ion–Linear Polyethylenimine–Polyacrylonitrile Blend for Solid Polymer Electrolytes

Abstract: Herein, we report the preparation and characterization of a novel polymeric blend between linear polyethylene imine (PEI) and polyacrylonitrile (PAN), with the purpose of facilitating the dissociation of lithium perchlorate salt (LiClO) and thus to enhance Li ion transport. It is a joint theoretical and experimental procedure for evaluating and thus demonstrating the lithium salt dissociation. The procedure implies the correlation between the theoretical pair distribution function (PDF) and conventional X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…It also showed a broad peak at a 2θ of 28 , which described the amorphous region. 40,50 We also observed that there were several diffractions in the XRD spectrum of NaI; these indicated the highly crystalline nature of the salt. 51 The diffraction peak of the sample without salt, N0, showed the overlap of the peak due to interactions between these two polymers and the copolymer as well as the NaI salt by blending.…”
Section: Dielectric Permittivity and Electric Modulus Studiesmentioning
confidence: 61%
See 1 more Smart Citation
“…It also showed a broad peak at a 2θ of 28 , which described the amorphous region. 40,50 We also observed that there were several diffractions in the XRD spectrum of NaI; these indicated the highly crystalline nature of the salt. 51 The diffraction peak of the sample without salt, N0, showed the overlap of the peak due to interactions between these two polymers and the copolymer as well as the NaI salt by blending.…”
Section: Dielectric Permittivity and Electric Modulus Studiesmentioning
confidence: 61%
“…From the XRD pattern of the PAN polymer, we observed that the characteristic peak at 17° indicated the semicrystalline nature and corresponded to the orthorhombic PAN (110) reflection. It also showed a broad peak at a 2θ of 28°, which described the amorphous region . We also observed that there were several diffractions in the XRD spectrum of NaI; these indicated the highly crystalline nature of the salt .…”
Section: Resultsmentioning
confidence: 80%
“…graphene, thiophene oligomers) ( Ling and Zhang, 2010 ; Yu et al, 2011 ; Ling et al, 2012 ; Ling et al, 2013 ; Huang et al, 2015 ; Kang et al, 2015 ; Zhang et al, 2016b ; Lombardi, 2017 ; Yilmaz et al, 2017 ; Liu et al, 2018 ) semiconductors is rising and appears to be a very promising technique to study h OI interfaces. Not only there is a vast experimental database that can be useful for vibrational modes assignment but also infrared and, to a lesser extent, Raman spectra can be easily computed using first-principles calculations ( Mombrú et al, 2017a ; Wang et al, 2020a ; Schöttner et al, 2020 ; Fernández-Werner et al, 2017 ; Pignanelli et al, 2017 ). Undoubtedly, nuclear magnetic resonance and X-ray photoelectron spectroscopies are other powerful tools to obtain chemical information about h OI interfaces but are less accessible than vibrational spectroscopies and computational calculations demand a high computational cost.…”
Section: Preparation Characterization and Computational Simulation Of...mentioning
confidence: 99%
“…High-resolution electron, atomic force and tunneling microscopies can give direct local information about h OI materials and interfaces but it is almost impossible to access a large amount of sample as in the case of using X-ray scattering techniques, thus both techniques should be complemented. Furthermore, the modeling of X-ray scattering data by using Rietveld (for crystalline) or Debye (for both crystalline and amorphous) methodologies are quite simple to perform and can be also assisted by classical molecular dynamics calculations ( Scardi and Gelisio, 2016 ; Fernández-Werner et al, 2017 ; Pignanelli et al, 2017 ; Bokuniaeva and Vorokh, 2019 ; Bertolotti et al, 2020 ).…”
Section: Preparation Characterization and Computational Simulation Of...mentioning
confidence: 99%
See 1 more Smart Citation